2020
DOI: 10.1128/iai.00105-20
|View full text |Cite
|
Sign up to set email alerts
|

Human Fallopian Tube Epithelial Cell Culture Model To Study Host Responses to Chlamydia trachomatis Infection

Abstract: Chlamydia trachomatis infection of the human Fallopian tubes can lead to damaging inflammation and scarring, ultimately resulting in infertility. To study the human cellular responses to chlamydial infection, researchers have frequently used transformed cell lines that can have limited translational relevance. We developed a primary human Fallopian tube epithelial cell model based on a method previously established for culture of primary human bronchial epithelial cells. After protease digestion and physical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 80 publications
1
12
0
1
Order By: Relevance
“…Our data demonstrate the following: (i) Ct developmental cycle in pOECs is productively completed within 48 hpi; (ii) pOECs mainly produce interferon regulated genes and T-cell attracting chemokines; and (iii) while Ct infection does not alter the overall mRNA and protein expression of CLDN-4, it leads to a temporary decrease in membrane-bound CLDN-4 with a coinciding increase of CLDN-4 within the Ct inclusion. Thereby, we have demonstrated that the Ct developmental cycle in pOECs as well as their immune response to infection is highly similar to what has previously been reported for their human cell counterparts [15]. We thereby establish pOECs as a relevant cell model for studies into Ct host-pathogen interactions.…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…Our data demonstrate the following: (i) Ct developmental cycle in pOECs is productively completed within 48 hpi; (ii) pOECs mainly produce interferon regulated genes and T-cell attracting chemokines; and (iii) while Ct infection does not alter the overall mRNA and protein expression of CLDN-4, it leads to a temporary decrease in membrane-bound CLDN-4 with a coinciding increase of CLDN-4 within the Ct inclusion. Thereby, we have demonstrated that the Ct developmental cycle in pOECs as well as their immune response to infection is highly similar to what has previously been reported for their human cell counterparts [15]. We thereby establish pOECs as a relevant cell model for studies into Ct host-pathogen interactions.…”
Section: Introductionsupporting
confidence: 77%
“…Yet, surprisingly, none of these cytokines were upregulated to a level that crossed the biological relevance threshold of 1.5× and significance level of p < 0.05 (Table 1). While this lack in upregulation was unexpected, these same cytokines were also not upregulated by Ct infection of primary human Fallopian tube epithelial cells [15]. Therefore, at least in vitro, genital tract epithelial cells might not be a primary source of pro-inflammatory cytokines in Ct infection.…”
Section: Innate Immune Response Of Porcine Oviduct Epithelial Cells To Chlamydia Trachomatis Infectionmentioning
confidence: 90%
See 2 more Smart Citations
“…Further studies are needed to exactly quantify the amount of the various fatty acids in L. crispatus BC1 BS, as well as to understand the mechanisms of action by which fatty acids counteract EBs infectivity. In this context, ex vivo and in vivo models, such as polarized human fallopian tube epithelial cells and animal models [ 43 , 44 ], could be employed to better represent the complexity of CT infection and improve translational relevance.…”
Section: Discussionmentioning
confidence: 99%